Gaya Kepemimpinan Terhadap Kepuasan Kerja Staf di Puskesmas - Muh Fauzar Al-Hijrah; Heriyati, Heriyati (Universitas Sulawesi Barat, 2021)
Leadership is important in an organization so that the goals of the organization can be achieved. Different leaders give different levels of job satisfaction to staff. The right leadership style is oriented towards creating job satisfaction. The research objective was to determine the relationship between leadership style and staff job satisfaction at the Sendana I health center in 2018. This study used quantitative research, in the form of a cross-sectional analytical survey. The sample collection technique used a total sampling of 73 people using a questionnaire instrument. The results of the Chi-square test obtained a value of ρ = 0.000 (<0.05) which means that there is a relationship between supportive leadership style and staff job satisfaction with job satisfaction, while the participatory leadership style shows that there is no positive relationship with job satisfaction with a value of ρ = 0.080. (> 0.05). Leaders need to pay attention to and evaluate complaints and the condition of their staff at work, it is hoped that they can build a better leadership style so that job satisfaction increases, such as applying discipline to staff / employees at Sendana I Health Center.